Penggunaan Bagian Stek Umbi Tanaman Gembili (Dioscoreaesculenta) dan Model Lanjaran Terhadap Produksinya - Walsen, Anthony; Lawalata, Imelda J; Nazara, Firman D (JURNAL BUDIDAYA PERTANIAN, 2024)
Lesser yam (Dioscorea esculenta) is a root crop which grows and spreads in various parts of Indonesia, from Papua to Sumatra. Plant support technique using stakes is a way to support physical plant growth to control shape, size, and direction of plants. This study aimed to obtain the tuber parts as propagules of lesser yam plant (Dioscorea esculenta) and the of stakes as plant support on lesser yam yield. The research experiment was carried out using a randomized block design (RBD) which consisted of 2 treatment factors; the first factor being the plant support techniques consisted of no support, single support, and pyramidal support model, and the second factor tuber parts as propagules consisted of root, middle, and tip root cuttings. The results showed that the interaction between the tuber cuttings and the plant support model was not significant or there was no synergistic in supporting the growth and yield in the form tubers, whereas the effect of tuber cutting treatments was significant on number of tubers (12 planted tubers) and highly significant on tuber weight (1864.9 g), tuber diameter (5.84 cm) and tuber length (6.11 cm). The effect of plant support models was not significant on number and weight of tubers, however was significant on the tuber diameter (5,54cm), and highly significant on the tuber length (6.05 cm).